CaCl2 in gerbera vase life: pigments, phenols, lignin and scape anatomy - González-Aguilar Susana; Zavaleta-Mancera, Araceli (Revista Mexicana de Ciencias Agrícolas, 2018)
Gerbera jamesonii has short vase life characterized by bending of floral stem (scape). With the purpose to extend gerbera vase life, three different CaCl2 concentrations (0.1, 0.5 and 1.0%) were tested in Duela and Shirlaine varieties. Weight loss of whole flower and ligules was less than in control with 0.5% and 1.0%concentrations. Whole flower and ligules weight was reduced with 0.5% and 1.0% concentrations when compared to control. 0.5% concentration was best treatment; it increased average vase life (25 d for Duela and 24 d for Shirlaine). Floral stems treated with built up CaCl2 more Ca+2 in apex (25.33 μg g-1 for Duela and 64.0 μg g-1 for Shirlaine), lasting erect longer than control (9.67 μg g-1 for Duela and 13.67 μg g-1 for Shirlaine). With 0.5% concentration a second experiment was performed to assess total carotenes, anthocyanins (pelargonidin, cyanidin) and phenols concentration changes in ligules. Shirlaine’s anthocyanins did not change in treatments. Phenols increased 21% in Shirlaine and 40% in Duela with regards their initial concentration, in contrast carotenes decreased 60% and 35% at the end of vase life, respectively. Interfascicular tissue is more lignified in cv Duela than in cv Shirlaine, giving it more resistance. The lignified relative area (%) on scape’s medium region was greater in Duela (7%) than in Shirlaine (4%). Greater stem resistance in Duela is explained by its anatomy and lignification, but in both varieties CaCl2 was effective to delay senescence and scape’s bent.